Vibration control of industrial robot arms by multi-mode time-varying input shaping. (January 2021) - Thomsen, Dan Kielsholm; Søe-Knudsen, Rune; Balling, Ole; Zhang, Xuping
Abstract : highlights: Vibration control of robot arm by Multi-Mode Time-Varying Input Shaping. Robot arm vibrational characteristics are estimated based on inertia. A complete dynamic map for real time evaluation is obtained within 72 minutes. Experimental implementation and validation in a commercial UR5e robot. Residual vibrations of industrial robot arm is reduced by up to 90%. Abstract: Robot arms exhibit non-ignorable residual vibration during point-to-point motion. Fractional Delay Time-Varying Input Shaping Technology (FD-TVIST) has previously been shown to reduce residual vibrations in robots arms, but requires an accurate estimate of the configuration dependent vibrational behavior. This paper presents a practical set of new tools for identifying and mapping the natural frequencies and damping ratios of dominant vibration modes of a robot arm with the commercial UR5e as a case. The new dynamic map is based on a physical interpretation of the robot arm, followed by strategic simplification. The new map of the vibration modes can be described by only 10 identified coefficients. Additionally, FD-TVIST is extended to the multi-mode case. The combination of new methods yields an efficient vibration suppression featuring short time delay, great robustness, simple implementation, low-cost computation, and insensitivity to trajectory generation method. Experimental implementation and validation in a commercial UR robot show that the residual vibration of the robot manipulator is reduced up to 90% with the developed vibration control method.